AB0089 Tofacitinib Mediates Synovial Angiogenesis in Psoriatic Arthritis. (10th June 2014) - Gao, W.; McCormick, J.; Connolly, M.; Veale, D.J.; Fearon, U.
Abstract : Background: Psoriatic Arthritis (PsA) is a common, chronic immune-mediated inflammatory disease, characterised by synovitis, progressive destruction of articular cartilage/bone, and is associated with psoriasis. Janus Kinase and Signal Transducer and Activator of Transcription (JAK/STAT), a critical signalling pathway involved in inflammatory mechanisms, has been implicated in the pathogenesis of PsA. Objectives: To examine the effect of Tofacitinib (A novel JAK inhibitor CP-690, 550) on pro-inflammatory pathways in PsA. Methods: Primary PsA synovial fibroblasts (PsASFC) and whole tissue PsA synovial explant cultures were established from PsA biopsies obtained at arthroscopy. Phospho-STAT3 and 1 (p-STAT3 and p-STAT1) expression were quantified by western blot in PsA synovial explants and PsASFC following culture in the presence of Tofacitinib (0.5μM and 1μM). The effect of Tofacitinib on PsASFC migration, invasion, matrigel network formation and MMP2/9 were quantified by wound repair assays, transwell invasion chambers and zymography. Cytokine expression of IL-6, IL-8 and IL-10 in ex-vivo synovial explants were assessed by ELISA. Results: Tofacitinib significantly decreased p-STAT3 and p-STAT1 expression in PsASFC and PsA synovial tissue explant cultures ex vivo . Tofacitinib significantly decreased spontaneous secretion of IL-6 (p<0.05), IL-8 (p<0.05) and induced IL-10 (p<0.05) expression in PsA explant cultures. Functionally, PsASFC invasion, matrigel network/tube formation, migration, and pro-MMP-2/-9 activities, were inhibited in the presence of Tofacitinib (p<0.05) Conclusions: This study demonstrates that Tofacitinib inhibits pro-inflammatory pathways in PsA, suggesting that JAK-STAT inhibition may be a potential therapeutic agent for the treatment of PsA. Disclosure of Interest: W. Gao: None declared, J. McCormick: None declared, M. Connolly: None declared, D. Veale Grant/research support: Abbvie, MSD, Pfizer, Roche, Consultant for: Pfizer, Roche, Speakers bureau: Abbott, MSD, Pfizer, Roche, U. Fearon: None declared DOI: 10.1136/annrheumdis-2014-eular.4256